The process of monitoring and evaluation of the Egyptian social pension program (al-daman al-igtimaay): An assessment - Soliman, Soha (AUC Knowledge Fountain, 2015)
This study focuses on one of the oldest social protection programs in Egypt, the social pension program (Al Daman Al-Igtimaay), implemented by the Egyptian Ministry of Social Solidarity (MoSS). It attempts to assess and analyze the extent of available monitoring and evaluation (M&E) processes in the social pension program applications and in some of Egypt’s relatively poorest governorates, Assiut and Qena. The main findings include the presence of baseline data on the families, some poverty indicators, and the presence of certain elements of monitoring and reporting. However, there’s a lack of key performance indicators, long and interim goals and targets, as well as having an intense focus on monitoring rather than evaluation. The findings showed that while there has been a growing importance for monitoring across different administrative levels; however, there’s a general lack and misdistribution of resources especially human and financial to conduct these activities. Finally the study also presents a historical moment of transition from the old social pension program to current reforms planned by the MoSS to correspond to the current context, as well as the aspirations and needs for improved developmental results.